Effect of Orange Scent on Preventing of Postpartum Depression: A Randomized Clinical Trial - Afsaneh Mahdizadeh; Mahin Tafazoli; Seyed Reza Mazloum; Ali Manteghi; Javad Asili; Mohammad Reza Noras (Mashhad University of Medical Sciences, 2018)
Introduction: Depression is one of the most common problems during pregnancy and after delivery. Research has shown that aromatherapy reduces women's mood disorders. Regarding the biological condition of postpartum period and reduced hormonal levels, this study was conducted with aim to evaluate the effect of orange scent on the prevention of postpartum depression. Methods: This clinical trial was performed in 2017 on 100 women who had delivery and had admitted to the gynecology section of Omolbanin hospital. The subjects were randomly divided to aromatherapy and control groups. The intervention group, in addition to receiving routine care, from the second day after delivery up to six weeks inhaled three drops of orange essence on the hanky every 12 hours. On days 10, 30, 42 after delivery, the Edinburgh Depression Inventory was completed in both groups. Those who obtained the score more than 12 in the questionnaire were referred to a psychiatrist and depression was diagnosed with clinical interview and based on the diagnostic criteria of DSM -4. Data was analyzed by SPSS software (version 16) and with statistical tests of Chi-square, repeated measures variance analysis, and Exact Fisher test. P<0.05 was considered statistically significant. Results: The mean score of depression was significantly reduced in the intervention group than the control group and the prevalence of depression at the end of the study was 0% in the aromatherapy group and 22.2% in the control group (p<0/001). Conclusion: Inhalation of orange scent in postpartum period is effective in preventing postpartum depression.